Periphrasis in the architectonics of media text - Bulakh, Maiia (Current issues of Ukrainian linguistics: theory and practice, 2017)
The paper focuses on the analysis of the periphrasis in the architectonics of media text. The author points out the functions of periphrases in the media text’s architectonics, in particular highlights functions of periphrasis-title. The research shows that the main functions of periphrases in architectonics of media text are as follows: a) periphrases logically connect parts of the text; b) periphrastic phrases disclose the contents, clarify concepts; c) due to their expressive potential periphrases distinguish accents, tagging the basic contents part of the text; d) periphrases allow fully realize the intention of the author of the material, identify the conceptual direction of the text, giving subjective evaluation, emotionally expressive, aesthetic characteristics of the text. Due to many different views on the definition of architectonic in linguistic studies, there is a problem of distinguishing the concept of "architectonic" and "structure" of the text. The author pays much attention to the peculiarities of architectonics of media text.